Dynamic of intra-continental extension in magmatic rift context: Turkana Rift (Northern Kenya) from Eocene to Present - (:unkn) unknown (My University, 2005)
Continental extension and rift geometry are controlled by the interaction of various parameters (thermal, mechanical, kinematical) that interplay at different spatial and temporal scales. In order to provide some new insights about the dynamics of rift segment evolution, this study focuses on the Turkana rift (Northern Kenya) which belongs to the eastern branch of the East African Rift System (EARS). This NS Cenozoïc rift portion developed since 45 Ma. and is unusual insofar as it is developed between the termination of two previous oblique cretaceous basins (N140°E Anza and Soudan). Its deep geometry is dominated by a set of syn-rift Oligocene-Miocene half-grabens, but since its present-day surface arrangement is marked by a subdued topography and it is characterised by weak seismicity, the definition of recent/active movements is not straightforward. This work, based on interpretation of Landsat ETM+ satellite imagery correlated with digital topography (SRTM) and seismic reflection dataset, leads us to propose and discuss a tectono-magmatic reconstruction of the poly-phased evolution of the Turkana rift from five successive ‘restored' maps (45-23 Ma., 23-15 Ma., 15-6 Ma., 6-2.6 Ma., 2.6 Ma.-Actual), combined with two additional maps dealing with pre-existing structures (Precambrian basement, previous Cretaceous rift). Our model fully demonstrates the influence of: 1) two regional-scale transverse corridors (NKFZ: N'Doto-Karisia N140°E, 100x600 km; KBFZ: Kataboi-Buluk N50°E, 30x250 km) and 2) magmatic domains on the nucleation and propagation of extensional structures during different stages of rifting. Both the locations of newly-formed basins and their final geometry is directly controlled by transverse fault zones. Syn-rift basins firstly develop within the N140°E NKFZ transverse corridor while they are locked by N50°E KBFZ structures that could also act as transfer zones. Relationships between magmati
Keywords: African Research